Smear slide descriptions of IODP Hole 386-M0095A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Descriptions of smear slides from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. This was followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the offshore phase, smear slides were prepared from paleontology samples collected with a tip-cut syringe from section ends every 5 m. During the onshore phase, smear slides samples were collected every 2 m to complement visual core description observations and identify the composition of fine-grained sediment. The smear slides were prepared by putting a small amount of sediment on a glass slide mixed with distilled water. The slide was subsequently evaporated on a hot plate, and the dried sample was mounted in Norland Optical Adhesive 61 using ultraviolet light. Sediment grain size and composition were examined under a polarized light petrographic microscope (Zeiss Axio Imager A1m POL-1) with an ocular micrometer. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023